Modern Stem Cell Therapy of Cardiac and Neurodegenerative Disorders: Pluses and Minuses: Pros and Cons of Stem cell therapy in cardio-neuro disorders - Irfan, Muhammad; Sajjad, Umar; Iqbal, Muhammad Naeem (PSM Biological Research, 2019)
Stem cell therapy is used for the treatment of many diseases like diabetes, ischemia, Parkinson’s disease, cardiac and neurodegenerative diseases. Stem cells can be differentiated into many new types as they are actually undifferentiated cells. Cardiac disease is a life-threatening disorder. Any type of injury to heart muscles increase risk factors for myocardial infarction. Studies indicate that different stem cells are used for the improvement of ventricular function by transplantation. New cardiac tissue cannot be formed but transplanted stem cells have paracrine effects that may be limited by teratoma formation. The brain has a specific formation of substitution connection to the confined and compact action of neuronal stem cells respectively. This demonstrates nervous abnormality and series of neurodegenerative infections that shows a critical civil issue of our inhabitants. So, competitive analysis is motivated using stem cell therapy as a key. Then comparisons of different studies for the treatment of different individuals who are suffering from neurodegenerative diseases are done. Different actions are taken that show aims for the charge of NP afflicted individuals. This review sums up the current scenario of stem cell therapy in Cardiac and Neurodegenerative disorders.